Natural-origin materials for tissue engineering and regenerative medicine - Silva, Simone Santos (2017)
Recent advances in tissue engineering and regenerative medicine have shown that combining biomaterials, cells, and bioactive molecules are important to promote the regeneration of damaged tissues or as therapeutic systems. Natural origin polymers have been used as matrices in such applications due to their biocompatibility and biodegradability. This article provides an up-to-date review on the most promising natural biopolymers, focused on polysaccharides and proteins, their properties and applications. Membranes, micro/nanoparticles, scaffolds, and hydrogels as biomimetic strategies for tissue engineering and processing are described, along with the use of bioactive molecules and growth factors to improve tissue regeneration potential. Finally, current biomedical applications are also presented.